Determining maximum push-off velocity in swimming using accelerometers - Stamm, A.; James, D. A.; Burkett, B. B.; Hagem, R. M.; Thiel, D. V. (Procedia Engineering, 2013)
The ability to unobtrusively measure velocity in the aquatic environment is a fundamental challenge for engineers and sport scientists. In the past video systems were the first choice to monitor the athletes during training. With the acceptance of small inertial sensors new ways of investigating the athletes movements have arisen. These small systems are light, easy to use and do not hinder the athlete during training, allowing an easy tracking of training improvements. This research used a self developed low-cost inertial sensor system, attached to the lower back, to record the acceleration of swimmers performing sub-surface wall push-offs. The recorded data were downloaded to MATLAB for data analysis. Using seven swimmers, the wall push-off velocity at three different efforts was analysed and compared to a tethered cable velocity meter (criterion measure) using Regression and Bland-Altman analysis. The maximum velocity determined from the accelerometer unit was linearly related to the benchmark criteria (r2=0.89). A biomechanical technique for the determination of the maximum glide velocity from acceleration data has been verified.